Urinary stone characteristics of patients treated with extracorporeal shock wave lithotripsy in Cipto Mangunkusumo Hospital Jakarta, 2008–2014: a gender analysis (Medical Journal of Indonesia, 2015)
Background: The incidence of urinary stone patient in Indonesia has increased every year in both genders. Data showed that urolithiasis was higher in male rather than female. The aimed of this study was to describe the characteristics of urinary stone found in patient who underwent extracorporeal shock wave lithotripsy (ESWL) at Cipto Mangunkusumo Hospital, Jakarta from 2008–2014. Methods: Data obtained from ESWL medical record Cipto Mangunkusumo Hospital, Jakarta from 2008–2014. We obtained 5,174 out of 6,020 data due to incompleteness data record. We sorted data records by gender, age, stone location, stone opacity, size of the stone, and history of ESWL, and analyzed by statistic tools (SPSS v 20 for Mac). Results: From 5,174 records, we found that the incidence of urinary stones was two times higher in male rather than female (66.3%:33.64%), occurred mostly in productive age (65.2% male, 65.9% female). Unilateral kidney stone was most common location found for both gender (50.2% male, 57.2% female), and most frequent site located in calyx inferior (24.8% male, 28.9% female). About 72.9% stone was radiopaque (73.7% male and 71.5% female). The mean size of the stone in male and female was 11.34±7.15 mm and 11.90±7.54 mm, respectively. This study also showed that 79.3% patients came for first ESWL. Conclusion: Urinary stone founds two times higher in male than female, and mostly occurs on their productive ages. Unilateral kidney stone in calyx inferior become the most common stone found in both gender. Most of the stone has radiopaque opacity.